International Solidarity Fund : inter-departmental correspondence - Parkin, E. G.
029-0025-001 I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From E. PARKIN Department FINANCE. To E.A. BELL Date 17th November, 1937. SUBJECT. INTERNATIONAL SOLIDARITY FUND. The attached is the full statement of donations and payments of the Spanish Workers' Fund from the commencement of the Appeal which was made in July, 1936, including the more recent Appeal in connection with the Basque Children's Fund. The whole of the donations have been set out on the right-hand side, and on the opposite side appears the total remittances to the I.F.T.U., Spanish Relief Committee, and the other Committees which are detailed, together with the total amount of the C.W.S., and other various payments which have been specified. The balances of the two Appeals appears at the foot of the left-hand side, but perhaps it would be a question of decision for the General Secretary as to whether these balances are communicated to the I.F.T.U. or whether the information which is sent to the I.F.T.U. will appear in this form. At any rate, I think that the details which Mr. Schevenels requires can be found readily in this account. E.P. 292/946/29/25